Food safety consciousness and consumers’ milk purchasing behavior: Evidence from a developing country - Thapa, Ganesh; Kumar, Anjani; Roy, Devesh; Joshi, Pramod Kumar (Cambridge University Press, 2020)
We study the effects of food safety awareness on consumers’ milk purchasing behavior in Nepal. We conducted consumer survey and employed an instrumental variable regression. We find education, income, and social network to influence food safety consciousness (FSC). Our results indicate the positive impact of FSC on weekly milk expenditure and probability of purchasing milk from milk cooperatives. Any policy that helps to improve the FSC levels will likely increase the purchase of safe milk from the modern market outlet, and lack of such awareness raising policies has prevented the market for safe food from evolving and expanding.